Analisis Nilai Moral dan Nilai Religius pada Syair Selawat Sunda di Desa Pamarayan Kecamatan Jiput Kabupaten Pandeglang serta Pemanfaatannya Sebagai Bahan Pembelajaran Syair di SMP - Adam, Fikri Rustam; Al Gadri, Henri Henriyan (Universitas Mathla'ul Anwar Banten, 2024)
the purpose of writing this thesis is to describe the message or meaning contained in the lyrics of Sundanese selawat in Pamarayan village, Jiput sub-district and its use as learning material in junior high schools. This research was conducted using a qualitative approach with descriptive methods that focused on content analysis. The data and data sources in this research are Sundanese selawat texts in Pamarayan village, such as: words or lyrics of Sundanese selawat. The instrument used in this research was the researcher himself with a theory validation test. Based on the description of the results of the analysis of moral values and religious values in Sundanese Selawat poetry in Pamarayan Village, Jiput District, Pandeglang Regency and its use as poetry learning material in junior high schools, several moral value messages were found in the lyrics of this Sundanese Selawat poetry, including: worship, pray, repent, be grateful, take care of yourself, be patient, not be greedy, not be arrogant, respect parents, respect teachers, and love peace. And several religious value messages were found in the lyrics of this Sundanese Selawat poetry, namely: repentance, patience and trust. The results of this research can be implied as learning material in junior high schools